2016
DOI: 10.1371/journal.pone.0165033
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Profiles in Women with PCOS and PCOS Offspring; A Pilot Study

Abstract: ObjectiveTo study metabolic/inflammatory biomarker risk profiles in women with PCOS and PCOS offspring.DesignCross-sectional comparison of serum biomarkers.SettingUniversity Medical Center Utrecht.PatientsHyperandrogenic PCOS women (HA-PCOS, n = 34), normoandrogenic PCOS women (NA-PCOS, n = 34), non-PCOS reference population (n = 32), PCOS offspring (n = 14, age 6–8 years), and a paedriatic reference population (n = 30).Main Outcome Measure(s)Clustering profile of adipocytokines (IL-1b, IL-6, IL-13, IL-17, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 53 publications
(60 reference statements)
3
52
0
3
Order By: Relevance
“…Though some information shows Th17 of PCOS is decreasing in animal models [74,75], in human PCOS, evidence focuses on the expansion of proinflammatory Th17 subset not only in the blood but also kidneys [75]; however, the reason is obscure. In this condition, IL-6 may inhibit TNFα production and also effectively drive angiogenesis, thus promoting the formation of blood vessels and increases the concentration of the folliclestimulating hormone [76]. It is confirmed that a significant difference in the Th17/Th2 ratio, with a bias toward Th17, is common among patients with PCOS [77].…”
Section: Mediators Of Inflammationmentioning
confidence: 92%
“…Though some information shows Th17 of PCOS is decreasing in animal models [74,75], in human PCOS, evidence focuses on the expansion of proinflammatory Th17 subset not only in the blood but also kidneys [75]; however, the reason is obscure. In this condition, IL-6 may inhibit TNFα production and also effectively drive angiogenesis, thus promoting the formation of blood vessels and increases the concentration of the folliclestimulating hormone [76]. It is confirmed that a significant difference in the Th17/Th2 ratio, with a bias toward Th17, is common among patients with PCOS [77].…”
Section: Mediators Of Inflammationmentioning
confidence: 92%
“…Reactive oxygen species-induced (ROS-induced) oxidative stress (OS) is a known activator of nuclear factor kappa-light-chain-enhancer of activated B cells (NF k B), inducing inflammatory responses [5]. Polycystic ovary syndrome (PCOS) is associated with chronic low-grade inflammation as demonstrated by elevated circulating inflammatory agents [32]. Obesity and hyperandrogenism stimulate chronic low-grade inflammation in polycystic ovarian syndrome women [32].…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is associated with chronic low-grade inflammation as demonstrated by elevated circulating inflammatory agents [32]. Obesity and hyperandrogenism stimulate chronic low-grade inflammation in polycystic ovarian syndrome women [32]. It is acceptable to propose that monocytes (MNC) recruited into the polycystic ovaries lead to a local inflammatory response that stimulates cytochrome P450 family 17 (CYP17), the ovarian steroidogenic enzyme, responsible for androgen synthesis [5].…”
Section: Discussionmentioning
confidence: 99%
“…These latter findings suggest that 437 the NIH and Rotterdam diagnostic criteria do not identify biologically distinct subtypes of 438 PCOS. There have been previous efforts to subtype PCOS using unsupervised clustering (25)(26)(27)(28), 439 but no subsequent investigation into the biologic relevance of the resulting subtypes. 440…”
Section: Subtypes In Pcos Families 398mentioning
confidence: 99%